Circulating Endothelial Progenitor Cells in Type 1 Diabetic Patients: Relation with Patients’ Age and Disease Duration - Arcangeli, Adolfo; Lastraioli, Elena; Piccini, Barbara; D’Amico, Massimo; Lenzi, Lorenzo; Pillozzi, Serena; Calabrese, Maria; Toni, Sonia; Arcangeli, Annarosa (Frontiers in Endocrinology, 2017)
Objectives: Circulating Endothelial Progenitor Cells (cEPCs) have been reported to be dysfunctional in Diabetes Mellitus (DM) patients, accounting for the vascular damage and the ensuing high risk for cardiovascular disease (CVD) characteristic of this disease. The aim of the present study was to evaluate the number of circulating cEPCs in type 1 DM (T1DM) patients, without clinical vascular damage, of different ages and with different disease duration. Methods: An observational, clinical-based prospective study was performed on T1DM patients enrolled in two clinical centers. cEPCs were determined by flow cytometry, determining the number of CD34/CD133/VEGF-R2 positive cells within peripheral blood mononuclear cells (PBMC). Results: The number of cEPCs was lower in adult T1DM patients, whilst higher in childhood/young patients, compared to controls of the same age range. When patients were grouped into two age groups ( or < 20 years) (and categorized on the basis of the duration of the disease), the number of cEPCs in young (< 20 years) patients was higher compared with older subjects, regardless of disease duration. A subset of patients with very high cEPCs was identified in the <20 years group. Conclusions: There is an association between the number of cEPCs and patients’age: childhood/young T1DM patients have significantly higher levels of cEPCs, respect to adult T1DM patients. Such difference is maintained also when the disease lasts for more than 10 years. The very high levels of cEPCs, identified in a subset of childhood/young patients, might protect vessels against endothelial dysfunction and damage. Such protection would be less operative in older subjects, endowed with lower cEPC numbers, in which complications are known to develop more easily.